Analisis Faktor yang Berhubungan dengan Kematian Maternal dalam Penguatan Pengetahuan dan Pengembangan Kebijakan Kesehatan: Studi Otopsi Verbal Maternal - Innama Sakinah; Ahmad Jubaedi; Fifi Musfirowati (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Several factors that cause maternal death can be prevented. To get overview of maternal death caused, it is necessary to carry out in-depth investigations to family and various related parties. This study aims to determine the profile of maternal deaths, the factors that cause maternal deaths that can be prevented and the obstacles that cause maternal deaths. This study used mixed methods with sequential explanatory. The quantitative approach in the first stage was collecting data from data recapitulation and OVM of 254 maternal deaths in Banten Province in 2021. The second stage used a qualitative approach through in-depth interviews. The results showed that 97.6% of maternal deaths could be prevented. The high number of maternal deaths caused by the lack of ANC visits, the referral factor is especially late in deciding to refer.